STATE AND PROSPECTS OF DEVELOPMENT OF INVESTMENT AND INNOVATION ACTIVITY OF MUNICIPAL COMMERCIAL ENTERPRISES OF MUNICIPAL ELECTRIC TRANSPORT - STAMATIN, VYACHESLAV; SUKHONOS, MARIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article provides a detailed analysis of the socio-economic significance of urban electric transport, separately considered its economic and social impacts on the urban economy. Addressing the crisis of urban electric transport, on the one hand, will lead to increased economic and business activity, and on the other - to social stability. It was found that any enterprise of urban electric transport can become an active participant in business activities, the purpose of which is to make a profit by carrying out production and other economic activities. The development of enterprises can be carried out on the basis of the principle of free choice of activities, as a result of which additional jobs can be created from profits, in addition, increase the economic and social working conditions of enterprises and increase public satisfaction by meeting its social needs. Also in the article the peculiarities of the activity of municipal commercial enterprises of urban electric transport and the state and prospects of development of their investment and innovation activity are revealed and described in detail. The common features, and hence the common problems of urban electric transport enterprises, the solution of which, according to the authors, is seen 1) in the implementation of full or partial commercialization of urban passenger transport; 2) its integrated development. The authors propose to focus on the second approach, which involves the development of an effective organizational and economic mechanism for managing innovation and investment activities of urban electric transport enterprises to improve the management of its work. Thus, overcoming the crisis of public transport companies will have a positive impact on the entire national economy.
Keywords: urban electric transport; investment and innovation activity; communal commercial enterprises; socio-economic activity; efficiency of transport functioning